The Effects of Disinfection Byproduct 2,6-Dichloro-1,4-benzoquinone on the Cyanobacterium Microcystis aeruginosa: From the Perspectives of Biochemistry and Non-Targeted Metabolomics - Tianqi Zhang; Zhaoyang Wang; Liang Wu; Chaonan Liu; Liang Meng; Fuxiang Tian; Meifang Hou; Haizhuan Lin; Jing Ye (Toxics)
2,6-Dichloro-1,4-benzoquinone (2,6-DCBQ) is an emerging chlorinated disinfection byproduct (DBP) in bodies of water. However, this compound poses an unknown toxic effect on cyanobacteria. In this study, the toxicological mechanisms of 2,6-DCBQ in Microcystis aeruginosa (M. aeruginosa) were investigated through physiological and nontargeted metabolomic assessments. The results show that 2,6-DCBQ inhibited the growth of M. aeruginosa, reduced its photosynthetic pigment and protein contents, increased the levels of reactive oxygen species, damaged the antioxidant defense system, and aggravated the cytomembrane. Meanwhile, 2,6-DCBQ stimulated the production and release of microcystin-LR (MC-LR) and altered the transcripts of genes associated with its synthesis (mcyA, mcyD) and transport (mcyH). In addition, nontargeted metabolomics of M. aeruginosa cells exposed to 0.1 mg/L 2,6-DCBQ identified 208 differential metabolites belonging to 10 metabolic pathways and revealed the considerable interference caused by 2,6-DCBQ among ABC transporters, the two-component system, and folate biosynthesis. This study deepens the understanding of the physiological and nontargeted metabolomic responses of M. aeruginosa exposed to 2,6-DCBQ, offers insights into the toxic effect of 2,6-DCBQ on M. aeruginosa, and provides a theoretical basis for the ecological risk assessment of emerging DBPs in accordance with water quality criteria.